A practical guide to the analysis of non-response and attrition in longitudinal research using a real data example - Eisner, Nora L.; Murray, Aja L.; Eisner, Manuel; Ribeaud, Denis (International journal of behavioral development, 2019)
Selective non-participation and attrition pose a ubiquitous threat to the validity of inferences drawn from observational longitudinal studies. We investigate various potential predictors for non-response and attrition of parents as well as young persons at different stages of a multi-informant study. Various phases of renewed consent from parents and young persons allowed for a unique comparison of factors that drive participation. The target sample consisted of 1675 children entering primary school at age seven in 2004. Seven waves of interviews, over the course of 10 years, measured levels of problem behavior as rated by children, parents, and teachers. In the initial study recruitment, where participation was driven by parental consent, non-response was highest amongst certain socially disadvantaged immigrant minority groups. There were fewer significant group differences at wave 5, when young people could be directly recruited into the study. Similarly, attrition was higher for some immigrant background groups. Methodological implications for future analyses are discussed.